Superstring compactifications with manifest spacetime supersymmetry - Daniel, Cassiano Antonio [UNESP] (UNESP, 2025)
This thesis explores the superstring compactified to four- and six-dimensional backgrounds. The theory is quantized using the spacetime supersymmetric hybrid formalism for the superstring while leveraging two-dimensional worldsheet methods. After the four-dimensional hybrid description is developed in an electromagnetic background, a superstring field theory action for the first massive states is constructed — both in superspace and in terms of the components fields. The action includes a massive spin-3/2 and a massive spin-2 field propagating in the presence of a constant non-zero U(1) gauge field. Quantization of the superstring compactified to a Calabi-Yau twofold can be achieved using the six-dimensional hybrid description. However, the hybrid formalism allows only half of the eight d = 6 N = 1 SUSYs manifest. We overcome this issue and extend the formalism such that all spacetime SUSYs can be made manifest. The BRST operator, physical states and a scattering amplitude prescription are explicitly constructed. We then study the Type IIB superstring in an Ad'S IND. 3' x 'S POT.3 background. By making use of the Berkovits-Vafa-Witten hybrid formalism for the pure NS-NS flux case, we compute a supersymmetric three-point amplitude of half-BPS vertex operators inserted on the Ad'S IND. 3' boundary. The computation is performed using the PSU(1, 1|2)-covariant variables. It is found that integrating out the fermionic worldsheet fields in the path integral gives rise to the target-space vielbein, which explicitly encodes that the conformal group on the boundary is identified with the symmetry group of the AdS bulk. The superstring in Ad'S IND. 3' x 'S POT.3 can be supported by a mixture of NS-NS and R-R self-dual three-form flux. We construct a manifestly PSU(1, 1|2) × PSU(1, 1|2)- invariant sigma-model action for the superstring in Ad'S IND. 3' x 'S POT.3 x ' T POT.4' with mixed flux. The model is then covariantly quantized and proven to be conformal invariant at the one-loop level. We conclude by showing how one can relate the supersymmetric description with the Berkovits-Vafa-Witten Ad'S IND. 3' x 'S POT.3 worldsheet action with mixed flux.

Esta tese explora compactificações da supercorda em espaços de quatro e seis dimensões. A teoria é quantizada utilizando o formalismo híbrido supersimétrico para a supercorda, ao mesmo tempo em que se utilizam métodos de teoria conforme em duas dimensões. Após o desenvolvimento da descrição híbrida em quatro dimensões acoplada a um campo eletromagnético, constrói-se uma ação de teoria de campos da supercorda para os primeiros estados massivos — tanto no superspaço quanto em termos dos campos componentes. A ação inclui um campo massivo de spin-3/2 e um campo massivo de spin-2 propagando na presença de um campo de gauge U(1) não nulo. A quantização da supercorda compactificada em um Calabi-Yau de duas dimensões complexas pode ser alcançada usando a descrição híbrida de seis dimensões. No entanto, o formalismo híbrido permite que apenas metade das oito SUSYs do superespaço d=6 N=1 estejam manifestas. Superamos essa limitação e estendemos o formalismo de forma que todas as SUSYs do espaço-tempo possam ser manifestas. O operador BRST, estados físicos e uma prescrição de amplitude são explicitamente construídos. Em seguida, estudamos a supercorda Tipo IIB em um espaço Ad'S IND. 3' x 'S POT.3. Utilizando o formalismo híbrido de Berkovits-Vafa-Witten para o caso de fluxo NS-NS puro, calculamos uma amplitude supersimétrica de três pontos de operadores de vértice half-BPS inseridos na fronteira de Ad'S IND. 3'. O cálculo é realizado em termos das variáveis covariantes de PSU(1,1/2). Encontramos que integrar os campos fermiônicos da supercorda na integral de caminho gera o vielbein do espaço-tempo, que codifica explicitamente que o grupo conforme na fronteira é identificado com o grupo de simetria do interior de AdS. A supercorda em Ad'S IND. 3' x 'S POT.3 pode ser descrita por uma mistura de fluxos de três-forma auto-duais NS-NS e R-R. Construímos uma ação de folha de mundo para a supercorda emAd'S IND. 3' x 'S POT.3 x 'T POT. 4' com fluxos mistos que é manifestamente invariante sob transformações de PSU(1, 1/2) x PSU(1, 1/2)$. Quantizamos covariantemente o modelo, demonstrando sua invariância conforme em um loop. Terminamos mostrando como é possível relacionar a descrição supersimétrica com a ação de folha de mundo de Berkovits-Vafa-Witten em Ad'S IND. 3' x 'S POT.3 com fluxos mistos.
Compactificações da supercorda com supersimetria espaço-temporal manifesta
Keywords: Teoria das supercordas; Supersimetria; Partículas (Física nuclear)